2019
DOI: 10.7762/cnr.2019.8.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Does Turmeric/curcumin Supplementation Change Anthropometric Indices in Patients with Non-alcoholic Fatty Liver Disease? A Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Curcumin is the principal polylphenol of turmeric that has been used to treat various disorders. However, its anti-obesity effects in patients with non-alcoholic fatty liver disease (NAFLD) remain controversial. Therefore, we aimed to perform a meta-analysis on the effects of supplementation with turmeric/curcumin on body weight, body mass index (BMI) and waist circumference (WC) in these patients. PubMed, Scopus, Cochrane Library, and ISI Web of Science were searched until January 2019, without any restrictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 60 publications
0
16
0
2
Order By: Relevance
“…No significant effect of turmeric/curcumin on body weight and BMI in NAFLD patients was described by Jafarirad et al [ 205 ]; however, the last dose–response meta-analysis [ 206 ] (n-8 RCTs) showed that curcumin might positively affect the visceral fat and abdominal obesity. The beneficial systemic/metabolic effects of orally administered curcumin are also related to their influence on the microbial community.…”
Section: New Dietary Perspectives In Nafld Treatment Via Gm Modulamentioning
confidence: 99%
“…No significant effect of turmeric/curcumin on body weight and BMI in NAFLD patients was described by Jafarirad et al [ 205 ]; however, the last dose–response meta-analysis [ 206 ] (n-8 RCTs) showed that curcumin might positively affect the visceral fat and abdominal obesity. The beneficial systemic/metabolic effects of orally administered curcumin are also related to their influence on the microbial community.…”
Section: New Dietary Perspectives In Nafld Treatment Via Gm Modulamentioning
confidence: 99%
“…Even though turmeric is believed has a good impact on health, but studies found that it has a side effect. It could cause headaches, rash, and diarrhea (Jafarirad et al, 2019).…”
Section: Traditional Medicationmentioning
confidence: 99%
“…Several systematic reviews of randomized controlled trials (RCTs) were conducted to evaluate the effects of curcumin supplementation on body composition including body weight, body mass index (BMI), and waist circumference [ 19 , 20 , 21 , 22 , 23 ]. Although most reviews included overweight or obese adults, some included participants with normal BMI [ 19 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%